Thermodynamic Investigations Of Pyrometallurgy Of Sulfide Concentrates - Vladimir Mindin (The Minerals, Metals and Materials Society, 1998)
This paper presents results of thermodynamic investigations and experimental' studies of some essential for pyrometallurgy of sulfide concentrates topics. Among them: 1. Thermodynamic simulation and experimental investigations of roasting process, 2. Thermodynamic investigations of sulfur dioxide off-gases treatment technologies. 3. Investigations on "Mind in -Kiknadze" effect of suppression of sulfur dioxide formation during sulfide concentrates roasting in the vapor containing atmosphere. 4. Thermodynamic simulation and experimental investigations of sulfide concentrates and manganese containing materials co-roasting processes. Some essential aspects of thermodynamic simulation techniques are also discussed.